Assessing risky and protective behaviors among pedestrians in the Dominican Republic: New evidence about pedestrian safety in the Caribbean. (September 2021) - Alonso, Francisco; Oviedo-Trespalacios, Oscar; Gene-Morales, Javier; Useche, Sergio A.
Abstract: Introduction: Research on pedestrians' behavior and safety in low and middle-income countries (LMICs) is scarce, compared to high-income economies. This study aimed to present the validation of the Walking Behavior Questionnaire (WBQ), which has not been tested before in the Dominican Republic, and to evaluate age differences in walking-related self-reported behaviors. Methods: For this study, a nationwide sample of 1026 pedestrians answered a questionnaire on risky and safe walking behaviors. Psychometric properties of the WBQ, variable correlations and age-based differences in walking were tested. Results: Overall, the WBQ presented an adequate structure, goodness-of-fit indexes, and high reliability. Significant correlations between walking-related variables and demographic factors, as well as key differences in walking behaviors among young people, adults, and aging adults were found. Conclusions: These results provide a strong background for assessing walking behaviors through the WBQ (for the first time in an LMIC), as -apart from presenting fair psychometric properties-it highlights the existence of walking pattern-related and demographic differences in the risky behaviors performed by pedestrians. Implications: In practical settings, this is the first large-scale behavioral questionnaire-based research on pedestrian safety conducted in the Dominican Republic, whose outcomes support the value of implementing effective evidence-based policies and educational interventions that consider age-related specificities for strengthening both healthier and safer walking. Furthermore, these implications may be applied in other countries of the region or with similar socio-economic features. Highlights: Pedestrians' walking behavior is a relevant issue for community health and safety. Validated tools for assessing pedestrian behaviors are scarce in emerging countries. This research presents the WBQ results in a Dominican Republic nationwide sample. Demographic differences have been found for risky walking behaviors, although not for protective ones. This study contributes to the implementation of pedestrian safety policies in the region.